Attitudes Toward Family-Based Treatment Impact Therapists’ Intent to Change Their Therapeutic Practice for Adolescent Anorexia Nervosa - Accurso, Erin C.; Le Grange, Daniel; Graham, Andrea K. (Frontiers in Psychiatry, 2020)
Community-based clinicians who treat patients with eating disorders rarely use empirically-supported treatments, and research demonstrates that clinicians make significant modifications when implementing family-based treatment (FBT) for anorexia nervosa. This study examined clinician attitudes towards FBT and explored the extent to which attitudes predicted intent to shift practices following training in FBT. Clinicians (N = 129) completed a standardized training in FBT for AN, either a two-day introductory training (n = 99) or a one-day “advanced” training (n = 30). Linear regressions were used to examine the association between therapists’ attitudes towards FBT and their intent to use strategies consistent with FBT in the future, adjusting for pre-training use of strategies. Providers reported very positive attitudes towards evidence-based practices in general and moderately positive attitudes towards FBT. There were no significant differences between “novice” and “advanced” providers on attitudes towards evidence-based practices or FBT (ps > .10). For the subset of providers attending their first training in FBT, more positive attitudes towards FBT significantly predicted greater intent to use FBT-consistent strategies (p = .004), and more positive attitudes towards evidence-based practice significantly predicted lesser intent to use FBT-inconsistent strategies (p = .009). This study suggests that both general attitudes towards evidence-based practice and specific attitudes towards FBT may impact implementation. Future research might examine whether a brief intervention to improve attitudes towards FBT might increase the likelihood of seeking expert consultation post-training.